Globalization and Income Inequality in Nigeria - Idongesit Udoh; Ubong Effiong; John Ekpe (International Journal of Management, Accounting and Economics, 2022)
The main objective of this study was to empirically examine the influence of globalization on income inequality in Nigeria from 1986 to 2021. The income inequality was represented by the Gini coefficient while globalization was measured by key indices like foreign direct investment, remittances, and trade openness. With the use of the autoregressive distributed lag (ARDL) approach which was as a result of the stationary of our series at levels and first difference as reported by the Augmented Dickey-Fuller unit root test, the study observed that a long-run relationship exists amid inequality and measures of globalization. In the short-run, it was realized that foreign direct investment, remittances, trade openness, and urbanization aided in reducing income inequality in the short-run while inflation accelerated income inequality within the study period. In the long-run, the only measure of globalization that significantly reduce income inequality is remittances; while foreign direct investment significantly increased income inequality in the long-run. the paper concluded that it is not inevitable that measures of globalization have different influence on inequality of income and wealth depending on time.